2022
DOI: 10.4103/jcd.jcd_150_22
|View full text |Cite
|
Sign up to set email alerts
|

Effect of triple antibiotic paste on the bond strength of epoxy and methacrylate resin-based sealers to root canal dentin

Abstract: Purpose: This study aimed to evaluate the effect of triple antibiotic paste (TAP) as an endodontic intracanal medicament on the bond strength of epoxy and methacrylate resin-based sealers to root canal dentin. Materials and Methods: In this in vitro study, 80 single-rooted human mandibular premolars were prepared using ProTaper rotary system. The specimens were randomly divided into a control group (without intracanal dressing) and an experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(36 reference statements)
0
0
0
Order By: Relevance
“…31 This finding was in agreement with the results of previous studies that reported higher bond strength of epoxy resinbased sealers compared with tricalcium silicate-based sealers. 18,28,[32][33][34] In the present study, the PBS in the coronal and middle thirds was higher than that in the apical third in all groups. Dentinal tubules are cleaner, larger, denser, and vertically more organized in the coronal and middle thirds, leading to increased dentinal tubule penetration of endodontic sealants and their bonding to root canal walls in these areas.…”
Section: Discussioncontrasting
confidence: 40%
“…31 This finding was in agreement with the results of previous studies that reported higher bond strength of epoxy resinbased sealers compared with tricalcium silicate-based sealers. 18,28,[32][33][34] In the present study, the PBS in the coronal and middle thirds was higher than that in the apical third in all groups. Dentinal tubules are cleaner, larger, denser, and vertically more organized in the coronal and middle thirds, leading to increased dentinal tubule penetration of endodontic sealants and their bonding to root canal walls in these areas.…”
Section: Discussioncontrasting
confidence: 40%